Impact of single dose of pegfilgrastim on peripheral blood stem cell harvest in patients with multiple myeloma or malignant lymphoma - Hideki Goto; Masashi Sawa; Shin-ichiro Fujiwara; Masaki Ri; Tadao Ishida; Masahiro Takeuchi; Kenji Ishitsuka; Masako Toyosaki; Kazutaka Sunami; Junichi Tsukada; Takashi Sonoki; Aiko Shimogomi; et al. (Scientific Reports)
Abstract This phase 2 study evaluated the impact of pegfilgrastim, a single-dose, long-acting granulocyte colony-stimulating factor, on the steady-state mobilization of hematopoietic stem cells into peripheral blood in patients with multiple myeloma (MM) or malignant lymphoma (ML). Efficacy and safety, along with CD34-positive cell mobilization outcomes were assessed in patients with MM, who were randomly assigned to pegfilgrastim (n = 30) or daily filgrastim (n = 31), and ML (pegfilgrastim only, n = 13) cohorts. In the MM cohort, CD34-positive cell counts ≥ 2 × 106/kg were achieved in 100% of patients in the pegfilgrastim group and 96.7% in the filgrastim group (difference: 3.3%; 80% confidence interval: −0.9–7.5%), demonstrating the non-inferiority of pegfilgrastim to filgrastim. All patients in the ML cohort achieved ≥ 2 × 106/kg CD34-positive cell counts. The plerixafor administration rates in the MM cohort were 50.0% and 63.3% in the pegfilgrastim and filgrastim groups, respectively, and 91.7% in the ML cohort. There were no major differences in safety measures between the two groups. Although the sample size was small, particularly in the ML cohort, a single dose of pegfilgrastim demonstrated comparable efficacy and safety to daily doses of filgrastim, indicating its potential for clinical use while reducing patient burden. Trial Registration: jRCT2011210029, NCT05007652.